Quantitative Analysis of the Correlation Between Islamic Religious Education Policy Implementation and Students’ Tolerant Attitude Development - Hary Nurdi; Dina Hermina; Nuril Huda (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to quantitatively analyze the correlation between the implementation of Islamic Religious Education (IRE) policy and the development of tolerant attitudes among secondary school students. The research is grounded in the importance of religious education in shaping students’ character and promoting religious moderation amid the rising cases of intolerance. A correlational quantitative method was employed using a Likert-scale questionnaire that measured both the implementation level of IRE policy and students’ tolerance attitudes. The sample was selected through simple random sampling from several secondary schools. The findings indicate a positive and significant correlation between IRE policy implementation and students’ tolerance levels, with dialogical learning and teacher role modeling emerging as dominant factors. These results highlight the importance of comprehensive implementation of IRE policy in fostering tolerant and moderate students